The Requiem of Taidam Ethnic Group: https://doi.org/10.69692/SUJMRD0802149 - CHANTANASIN, Bounkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The objective of this study is to analyze the pattern of using spoken words and life styles of Taidam ethnic group through the requiem. The sample of the study includes 485 words and 147 texts in the requiem of Taidam ethnic group. The study is analyzed by qualitative method under the concept of Jaralvilai CHARUNROCHANA, Souk XAIYALEUD, Phonesiri OUTHAIVANH and faculty, Onekeo NUANNAVONG and faculty, Khamhoung SANMANI, and Houmphanh RATTANAVONG. The results of the study has found that in the patterns of using words there were 7 patterns; such as, there were the majority of 14 duplicated words; 49 overlapping words 119 hyponymy 17 polysemy words, In addition, it is found that there are 286 dialect words, among those, there are 67 words used in the religious requiem; there are 35 antonym words that have 18 pairs of words; and there are 97 group of words that have 12 words of head word group and 87 words of sub word group. For life style, such as belief, Taidam ethnic group believes in the spirit or ghost such as the spirit of house, the protected spirit at bath river bank, the protected ghost at the ghost district gate, Maebao sipirit, a deity or spirit of heaven, mermaid, and soul of beginning and ending. Furthermore, Taidam ethnic group has yet believed in the prediction of being reborn of the dead’s spirit. The tradition of Taidam still includes prediction of ghost, funeral ceremony, Baci ceremony, prohibitive practice, shelf of ghost by family. Sending off the spirit has three shelves including sending to Damdoi, sending Lienparnnoy and sending to Lienparnluang.